2015
DOI: 10.1155/2015/141363
|View full text |Cite
|
Sign up to set email alerts
|

KIR Genes and Patterns Given by the A Priori Algorithm: Immunity for Haematological Malignancies

Abstract: Killer-cell immunoglobulin-like receptors (KIRs) are membrane proteins expressed by cells of innate and adaptive immunity. The KIR system consists of 17 genes and 614 alleles arranged into different haplotypes. KIR genes modulate susceptibility to haematological malignancies, viral infections, and autoimmune diseases. Molecular epidemiology studies rely on traditional statistical methods to identify associations between KIR genes and disease. We have previously described our results by applying support vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Traditional statistical techniques are used in molecular epidemiology investigations to find links between KIR genes and disease. Compared to healthy donors, patients with hematological malignancies had a higher prevalence of KIR2DL2 74 . The potential immunologic mechanisms underlying some KIR genes' higher prevalence in hematologic patients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Traditional statistical techniques are used in molecular epidemiology investigations to find links between KIR genes and disease. Compared to healthy donors, patients with hematological malignancies had a higher prevalence of KIR2DL2 74 . The potential immunologic mechanisms underlying some KIR genes' higher prevalence in hematologic patients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 95%
“…Compared to healthy donors, patients with hematological malignancies had a higher prevalence of KIR2DL2. 74 The potential immunologic mechanisms underlying some KIR genes' higher prevalence in hematologic patients compared to healthy individuals. In contrast to people without known pathology, patients with AA and ALL were significantly more susceptible to the KIR genes (KIR2DL5, KIR2DS1, KIR2DS3, and KIR3DS1 for AA), and AML and MDS did not appear to be similarly affected.…”
Section: Discussionmentioning
confidence: 99%
“…EBV-positive HL is more frequent in childhood, in older adults (>45 years) and in mixed cellularity cases. The survival of EBV-positive HL in the elderly and the immunosuppressed is particularly poor (7). For the young adults, it has been further suggested that delayed exposure to a common childhood pathogen may play a role in disease ©Annals of Tropical Medicine & Public Health S171 pathogenesis( 7) , ( 8) , (9).Increased knowledge of the virus' role in the basic biology of HL may generate novel therapeutic strategies for EBV-positive HL and the presence of EBV-latent antigens in the malignant HL cells may represent a target for cellular immunotherapy.…”
Section: Introductionmentioning
confidence: 99%